Transition Strategies of Change Management For the Succesful Implementation of Data Warehouse of Higher Education in Indonesia - Ade Rahmat Iskandar; Ari Purno (Telkom University, 2018)
Data Warehouse of Higher Education offers enormous advantages in efficiency, productivity, cost reduction and information integration system. This paper conducted to support success transition of implementation of Data Warehouse of Higher Education in Indonesia (that is called ‘Sistem Pangkalan Data Pendidikan Tinggi or PD-DIKTI in Indonesian) that had been implemented since 2013 ago. However, Data Warehouse of Higher Education implementations are complex, with many encountering difficulty and even failure. Transition of Data Warehouse implementation has been identified as critical success factor. A model that is used to manage the transition of Data Warehouse of Higher Education is Bridge’s Model, where this model is included to top ten leading transition for managing change in the world. The paper is going to summerize the results of a selected relevant articles both of the success implementation new IT technology and how to handle resistance to make transition hoped. In addition, we need to look at the transition models. The paper is hopefully able in changing the better equipped management to get satisfactory decision for all involved in implementing new IT system. This paper also conducted with Action research to get the information trusted.